Climacteric Symptoms and Sexual Dysfunction: Association between the Blatt-Kupperman Index and the Female Sexual Function Index - Cruz, Emanuela Fonseca; Nina, Vinícius José da Silva; Figuerêdo, Eduardo Durans (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2017)
Objective To investigate the association between the intensity of climacteric symptoms and sexual dysfunction in women aged 40 to 65 years.Methods Observational, analytic, cross-sectional study conducted with 63 women aged 40 to 65 treated at the gynecology outpatient clinic of a public hospital in northeastern Brazil. A questionnaire was used to collect identification data, clinical information, gynecological-obstetric data, lifestyle traits and information on chronic diseases. Climacteric symptoms and sexual function were evaluated by means of the Blatt-Kupperman index and the Female Sexual Function Index (FSFI) respectively. The association between the two indices was investigated using the chi-squared test; the difference in mean scores on the FSFI as a function of menopausal status was evaluated by Student's t-test. The significance level was set to p < 0.05.Results The mean value of the Blatt-Kupperman index was 26.42 (standard deviation [SD]: 4.52); 36.51% of the women exhibited severe symptoms. The mean score on the FSFI was 21.84 (SD: 4.11). More than half of the analyzed women (58.73%) exhibited sexual dysfunction (FSFI ≤ 26.5). Regarding the association between the Blatt-Kupperman index and the FSFI, the greater the intensity of the climacteric symptoms (Blatt-Kupperman), the higher the frequency of sexual dysfunction (FSFI). Sexual dysfunction was exhibited by 100% of the participants with severe climacteric symptoms, 70.59% of those with moderate symptoms, and only 9.09% with mild symptoms (p < 0.001).Conclusions The application of the Blatt-Kupperman index and of the FSFI allowed the detection of an association between the severity of climacteric symptoms and the prevalence of sexual dysfunction.
Keywords: climacteric; sexual dysfunction; hypoestrogenism; menopause; women's health